The Effect of Different Thawing Rates on Cryopreserved Human Iliac Arteries Allograft's Structural Damage and Mechanical Properties. (8th October 2020) - Novotny, Robert; Mericka, Pavel; Chlupac, Jaroslav; Matejka, Roman; Kristek, Jakub; Marada, Tomas; Konarik, Miroslav; Ivak, Peter; Sterba, Lubomir; Hlubocky, Jaroslav; Pirk, Jan; Janousek, Libor; et al.
Abstract : Introduction . The rate of thawing of cryopreserved human iliac arteries allografts (CHIAA) directly affects the severeness of structural changes that occur during this process. Method . The experiment was performed on ten CHIAA. The 10% dimethylsulphoxide in 6% hydroxyethyl starch solution was used as the cryoprotectant; all CHIAA were cooled at a controlled rate and stored in the vapor phase of liquid nitrogen (-194°C). Two thawing protocols were tested: (1) placing the CHIAA in a water bath at 37°C, and (2) the CHIAA were thawed in a controlled environment at 5°C. All samples underwent analysis under a scanning electron microscope. Testing of the mechanical properties of the CHIAA was evaluated on a custom-built single axis strain testing machine. Longitudinal and circumferential samples were prepared from each tested CHIAA. Results . Ultrastructural analysis revealed that all five CHIAA thawed during the thawing protocol 1 which showed significantly more damage to the subendothelial structures when compared to the samples thawed in protocol 2. Mechanical properties: Thawing protocol 1—longitudinal UTS 2, 53 ± 0, 47 MPa at relative strain 1, 27 ± 0, 12 and circumferential UTS 1, 94 ± 0, 27 MPa at relative strain 1, 33 ± 0, 09 . Thawing protocol 2—longitudinal ultimate tensile strain (UTS) 2, 42 ± 0, 34 MPa at relative strain 1, 32 ± 0, 09 and circumferential UTS 1, 98 ± 0, 26 MPa at relative strain 1, 29 ± 0, 07 . Comparing UTS showed no statistical difference between thawing methods. Conclusion . Despite the significant differences in structural changes of presented thawing protocols, the ultimate tensile strain showed no statistical difference between thawing methods.